Estudo fitoquímico de justicia acuminatissima (Acanthaceae) : caracterização química, avaliação biológica, contaminação fúngica e detecção de produtos radiolíticos - Geone Maia Correa (2013)
Justicia acuminatissima (Acanthaceae) is a medicinal plant, popularly known as "sara-tudo". This species is widely used in the Amazon region to relief inflammatory processes. The literature does not describe chemical and biological studies for this species. This study aimed to conduct chemical and pharmacological studies that prove their scientific use. Leaves and twigs were collected in Itacoatiara city - Amazonas state.After drying and grinding the material (separately) was performed the maceration with ethanol and ethanol 70% (v/v), yielding the respective crude extract. The leaf and twigs extracts obtained in ethanol were fractionated with solvents in an order of increasing polarity, such as hexane, dichloromethane, ethyl acetate, and methanol. Thus fourfractions from the leaves and four fractions from the twig were obtained.Phytochemical studies of the hexane fractions of leaves and twigs of J.acuminatissima provided sitosterol, a mixture of stigmasterol with sitosterol, lupeol, acyl-lupeol, friedelin, friedelinol, mixture of á-amyrin and lupeol, betulinic acid and the mixture of erythrodiol with betulin. The fractions of ethyl acetate from the leaves and twigs provided the isolation of a mixture of stigmasterol and sitosterol glucoside, besides the 4-hydroxy-benzoic acid and new alkaloid (3-ethyl-8-oxa-3-azabicyclo [3,2,1] octane- 1,6,7-triol. A mixture of á-glucose and â-glucose, sucrose was isolated from the methanol extract of the leaves. Study of aqueous extract of leaves of J. acuminatissima was performed by HPLCanalysis. As a result, a new derivative of luteolin glycosides was isolated: luteolin-3'-Oxylofuranoside. In addition, three other luteolin glycoside derivatives were obtained for the first time for the Justicia: luteolin-5-O-rutinoside, luteolin-7-O-rutinoside, and luteolin-7-O-glucoside. Theoretical studies were performed to flavonoids. These analyzes allowed the elucidation of these compounds.The polar extract, nonpolar extract and some triterpenes and flavonoids exhibited antimicrobial and anti-inflammatory activities. Furthermore, the ethyl acetate fraction showed a expressive antimicrobial activity against E. coli and C. albicans. The dichloromethane fraction of leaves presented a 60% higher activity against all microorganisms tested using the same concentration of 250 ìg.mL-1. The fractions FAF, FDF, FMF, FF, lupeol, luteolin-3'-O-xylofuranoside, and the mixture of â- sitosterol/stigmasterol showed a significative reduction in the inflammatory process ofrats paws. It is worth highlighting that during the studies with J. acuminatissima was performed HPLC analysis to check for possible chemical changes after use of gamma rays as a decontamination method of this species. As a result, it was found that thegamma radiation up to 20 kGy did not interfere in the chemical integrity of J. acuminatissima. Furthermore, it was observed that a dose of 3.0 kGy was enough for the elimination of Aspergillus aculeatus, predominant fungi on the leaves of the species studied.